Lim0.5mn1.5o4-Δ (M = Co or Fe) Spinels with a High Oxidation State Obtained by Ultrasound-Assisted Thermal Decomposition of Nitrates. Characterization and Physicochemical Properties - Gautier-Zamora, J; Gautier-Zamora, J; Escrig-Murua, J; Alburquenque-Munoz, D; Alburquenque-Munoz, D; Márquez-Mandiola, P; Márquez-Mandiola, P (Academic Press, 2020)
Manganese lithium oxides with spinel-related structure, LiCo0.5Mn1.5O4-δ and LiFe0.5Mn1.5O4-δ, have been synthesized for the first time using an ultrasound-assisted thermal decomposition of nitrates (UA-TDN) synthesis method. The materials were studied by X-ray powder diffraction, scanning and transmission electron microscopy, oxygen stoichiometry determinations, Raman and X-ray photoelectron spectroscopy. The Rietveld refinement of the X-ray diffraction data indicated that the samples crystallize in the Fd3‾m space group which is characteristic of the cubic spinel structure and have a cell parameter of 0.8117 ​nm (LiCo0.5Mn1.5O4-δ) and 0.8254 ​nm (LiFe0.5Mn1.5O4-δ). The Scherrer method and the Williamson-Hall (W–H) method were used to evaluate the crystallite sizes. Energy-dispersive X-ray spectroscopy analyses confirmed that the metals were present in the expected stoichiometry. Scanning and transmission electron microscopy images showed that the particles are of an irregular polyhedral shape, having average sizes of 600 and 750 ​nm for the Co- and Fe-containing materials, respectively. X-ray photoelectron spectroscopy measurements revealed the presence of metal cations in high oxidation states: Co3+, Fe3+, Mn3+ and Mn4+. Considering the ensemble of the results obtained, it is possible to propose the following ionic distributions Li+[Co0.5 3+Mn0.6 3+Mn0.9 4+]O3.95 2− and Li+[Fe0.5 3+Mn0.5 3+Mn1.0 4+]O4 2−. © 2020 Elsevier Inc.